1985
DOI: 10.1182/blood.v65.2.283.283
|View full text |Cite
|
Sign up to set email alerts
|

Microrheologic investigation of erythrocyte deformability in diabetes mellitus

Abstract: This study was undertaken to determine whether diabetes alters the viscoelastic properties of erythrocytes. The oldest and youngest 10% fractions of circulating red cells were separated by centrifugation of freshly drawn blood obtained from ten diabetics with disease of one to 20 years' duration and from an equal number of age- and sex-matched control subjects. Cells from each fraction were suspended in phosphate- buffered saline, and their rheologic behavior was examined in a rheoscope. The elongation of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Alterations of mechanical properties of individual cells can reveal important information about changes in these networks. Studies of a variety of diseases utilizing different experimental techniques have shown that abnormalities in the elastic properties of individual cells are important in tissue homeostasis, cell growth, division and motility 37 and is also associated with disease pathogenesis and progression 38 39 40 41 42 . For example, as cells transform from non-malignant to cancerous phenotype, their cytoskeletal structure changes from an organized to an irregular network, and this change subsequently reduces the stiffness of these cells 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of mechanical properties of individual cells can reveal important information about changes in these networks. Studies of a variety of diseases utilizing different experimental techniques have shown that abnormalities in the elastic properties of individual cells are important in tissue homeostasis, cell growth, division and motility 37 and is also associated with disease pathogenesis and progression 38 39 40 41 42 . For example, as cells transform from non-malignant to cancerous phenotype, their cytoskeletal structure changes from an organized to an irregular network, and this change subsequently reduces the stiffness of these cells 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Incubation of DM1 erythrocytes with either C-peptide or insulin has been shown to improve both Na ϩ /K ϩ -ATPase activity and erythrocyte deformability (20,29,31). In DM2, impaired erythrocyte deformability remains controversial, as several groups have observed reduced deformability, while other reports do not confirm this finding (8,48). Although coadministration of C-peptide with insulin at a 1:1 ratio (1 nM of each peptide) rescues low O 2 -induced ATP release from DM2 erythrocytes, the 1:1 ratio had no effect on DM2 erythrocyte deformability (38).…”
Section: R415 C-peptide Signaling In Human Rbcsmentioning
confidence: 99%
“…All of the tasks performed by cytoskeletal elements are finely tuned, regulated, and synchronized with the overall function of a specific cell. Consequently, changes to cellular function during differ-entiation (Olins et al, 2000) or due to disease are mirrored in the cytoskeleton: Cytoskeletal alterations cause capillary clogs in circulatory problems (Worthen et al, 1989) and various blood diseases including sickle-cell anemia, hereditary spherocytosis, or immune hemolytic anemia (Bosch et al, 1994;Williamson et al, 1985), and genetic disorders of intermediate filaments and their cytoskeletal networks lead to problems with skin, hair, liver, colon, and motor neuron diseases such as amyotrophic lateral sclerosis (Fuchs and Cleveland, 1998;Kirfel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%